Architecture RePerformed the politics of reconstruction - Mager, Tino 19XX- (Ashgate, 2015)
First emerging at the beginning of the twentieth century, architectural reconstruction has increasingly become an instrument to visually revive a long bygone past. This book deals with the phenomenon of meticulous reconstruction in architecture. It argues that the politics of reconstruction go far beyond aesthetic considerations. Taking architecture as a major source of history and regional identity, the impact of large-scale reconstruction is deeply intertwined with political and social factors. Furthermore, memories and associations correlated with lost buildings of a bygone era are heavily influenced by their re-appearance, something which often contradicts historical events. Reconstruction has become an established way of building and dealing with the past, yet so far, there is no comprehensive scientific study on it